EFEKTIFITAS TERAPI AFIRMASI POSITIF DAN RELAKSASI TERHADAP PENURUNAN TINGKAT STRES PADA SISWA SEKOLAH DASAR - Prima Trisna Aji; Elinda Rizkasari (JURNAL SINEKTIK, 2021)
Stress is the body's reaction to situations that seem dangerous or difficult, stress makes the body produce the hormone adrenaline which functions to defend itself. This situation can result in the emergence of quite a number of symptoms, such as depression, irritability, anxiety, low quality of work. There are many obstacles faced by elementary school students facing the Final School Assessment such as anxiety, fear of not going to class, difficulty in learning concentration, laziness, low motivation, and the prevalence of gadget addiction. One of the tests to reduce stress levels is positive affirmation therapy and progressive muscle relaxation therapy. The purpose of this study was to determine the effectiveness of therapy on stress levels in elementary school students. The research design used a quasi-experimental method. The sample data collection technique used formula for pretest and posttest research by measuring using a questionnaire before and after therapy with a sample of 62 people. The results of bivariate analysis showed the effect of therapy with the Mann Whitney statistical test on stress levels in the therapy group with a p value of 0.000 > 0.05, in respondents.